Ecological prognosis modelling of benthos state in the Northern Caspian Sea - G. M. Abdurahmanov; E. A. Sokol'skaya; A. F. Sokol'skii (Юг России: экология, развитие)
There’s made an attempt in the work to estimate the bentos population of the Northern Caspian Sea by mathematic modelling methods. At use of the given method probably considerably to improve the forecast of the general admissible fishes in this area.